An empirical study of land rental development in rural Gansu, China: The role of agricultural cooperatives and transaction costs. (October 2021) - Li, Xinyi; Ito, Junichi
Abstract: The land rental ratio in China has increased significantly over recent years, with the national average reaching 37% in 2017. A significant body of literature has analyzed the driving force behind this movement; however, there still remains much to be learned about the land rental markets in rural China. This paper analyzes the factors that influence the land exchange in Gansu province whose land rental ratio was among the lowest in China at the start of the 2010s. Our contribution to the literature is to provide empirical insights into the factors that promote and impede the development of land rental markets. To this end, we estimate the land rental ratio equation using a panel dataset of 86 counties in Gansu province. The identification strategy is an application of the instrumental variable estimation method based on a fixed effects model. We draw the following conclusions from the analysis. First, agricultural cooperatives have a positive impact on the land rental development, suggesting that non-farm household producers are the major contributors to the demand side of farmland exchange. Second, transaction costs have a detrimental effect on land exchange, as theoretically supported by this study as well as empirical finding in the literature. Accordingly, the public organizations and/or rural collective play a vital role in reducing the transaction costs arising from land use disputes among lessors and lessees. Highlights: The land rental ratio in China has increased significantly over recent years. We estimate the land rental ratio equation using the IV method to correct the potential bias stemming from unobservables. The agricultural cooperatives are the major contributors to the demand side of farmland exchange. The public organizations play a vital role in reducing the transaction costs arising from land use disputes.